Flow Synthesis of Triptycene via Triple Cycloaddition of Ynolate to Benzyne - Iwata, Takayuki; Yoshinaga, Tatsuro; Shindo, Mitsuru (Synlett, 2020)
Flow synthesis of triptycene was achieved using triple cycloaddition of ynolate to benzyne. Employing the borate-type benzyne precursor, side reactions triggered by the addition of alkyllithium to benzyne were efficiently suppressed under microflow conditions, thus producing triptycene with a higher yield than that obtained under the corresponding batch conditions. Furthermore, ynolate prepared from α,α-dibromoester under microflow conditions was continuously added to the flow reaction with benzyne, which successfully synthesized triptycene in only one minute.
Keywords: triptycene; ynolate; benzyne; flow synthesis; cycloadditionborate